Hospitality industry managerial accounting - Schmidgall, Raymond S. 1945- (American Hotel & Lodging Educational Institute, 2016)
"The eighth edition reflects changes based on the 11th Revised Edition of the Uniform System of Accounts for the Lodging Industry that went into effect in January 2015, as well as major changes made to tax laws since the previous edition. Information on pricing and balance sheets has been updated, and industry statistics reflect the most recent 2014 hospitality data"--Provided by publisher.